2007
DOI: 10.1002/jpln.200625105
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plant growth–promoting rhizobacteria on growth and enzyme activities in wheat and spinach plants

Abstract: A pot experiment in a greenhouse was conducted in order to investigate the effect of different N2‐fixing, phytohormone‐producing, and P‐solubilizing bacterial species on wheat and spinach growth and enzyme activities. Growth parameters and the activities of four enzymes, glucose‐6‐phosphate dehydrogenase (G6PD; EC 1.1.1.49), 6‐phosphogluconate dehydrogenase (6PGD; EC 1.1.1.44), glutathione reductase (GR; EC 1.8.1.7), and glutathione S‐transferase (GST; EC 2.5.1.18) were determined in the leaves of wheat (Triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(43 citation statements)
references
References 43 publications
6
33
2
2
Order By: Relevance
“…The application of the combination of PGPR and mycorrhizal fungi alleviates the stress conditions, as reported by Nadeem et al, via the regulation of hormones, nutrition uptake and growth [124]. Similar outcomes have been reported by Cakmakci et al for wheat and spinach plants [77].…”
Section: Alleviation Of Abiotic Stress In Wheat By Pgprsupporting
confidence: 75%
See 1 more Smart Citation
“…The application of the combination of PGPR and mycorrhizal fungi alleviates the stress conditions, as reported by Nadeem et al, via the regulation of hormones, nutrition uptake and growth [124]. Similar outcomes have been reported by Cakmakci et al for wheat and spinach plants [77].…”
Section: Alleviation Of Abiotic Stress In Wheat By Pgprsupporting
confidence: 75%
“…The highest concentration of IAA is produced by bacterial strain P. fluorescens and Kocuria varians [74]. Specifically for wheat, the positive effect of PGPR via IAA has been reported [75][76][77][78].…”
Section: Production Of Plant Hormones and Other Beneficial Plant Metamentioning
confidence: 99%
“…This variation is attributed to the various biosynthetic pathways, location of the genes involved, regulatory sequences, and the presence of enzymes to convert active free IAA into conjugated forms (Patten and Glick, 1996). The production of IAA by bacteria isolated from rhizosphere of different crops, i.e., peanut, maize, wheat, and rice had already been reported in number of studies (Dey et al, 2004; Cakmakci et al, 2007; Mehnaz et al, 2010). The amount of IAA detected in the present study (with and without tryptophan) seems relatively higher than reported earlier, indicating that soils under investigation have bacteria that have the characteristics most commonly sought for use in growth enhancement of plants.…”
Section: Discussionmentioning
confidence: 93%
“…Selected strains, which were high carbon utilizing and phosphate solubilizing strains belonging to B. cereus, B. subtilis, B. megaterium, Pb. polymyxa, P. fluorescens, P. putida, S. maltophilia and B. cepacia, have been reported as good phosphate solubilizers and plant growth promoters (Chen et al 2006;Çakmakçı et al 2007b;de Freitas et al 1997;Dias et al 2009;Hariprasad and Niranjana 2009;Hoberg et al 2005;Idris et al 2009;Poonguzhali et al 2006). The carbon utilizations of PSB were investigated by using a Biolog microplate to determine if there are differences in the carbon utilizations of selected strains of these species.…”
Section: Discussionmentioning
confidence: 99%